Prediagnostic body size and risk of amyotrophic lateral sclerosis death in 10 studies. Issue 5 (3rd July 2018) - O'Reilly, Éilis J.; Wang, Molin; Adami, Hans-Olov; Alonso, Alvaro; Bernstein, Leslie; van den Brandt, Piet; Buring, Julie; Daugherty, Sarah; Deapen, Dennis; Freedman, D. Michal; English, Dallas R.; Giles, Graham G.; et al.
Abstract: Objectives and Methods : Using pooled multivariable-adjusted rate ratios (RR), we explored relationships between prediagnostic body-mass-index (BMI), waist-to-hip-ratio (WHR), and weight-gain during adulthood, and ALS in 419, 894 women and 148, 166 men from 10 community-based cohorts in USA, Europe, and Australia; 428 ALS deaths were documented in women and 204 in men. Results : Higher mid-to-later adulthood BMI was associated with lower ALS mortality. For 5 kg/m 2 increased BMI, the rate was 15% lower (95% confidence interval [CI]: 4–24%;  p  = 0.005). Although a clear linear trend was not evident for WHR at enrollment ( p  = 0.099) individuals in the highest cohort-specific quartile had 27% (95% CI: 0–47%; p  = 0.053) lower ALS compared to those in the lowest. BMI in early adulthood did not predict ALS; fewer than 10% of participants had early adulthood BMI >25 kg/m 2, limiting power. Weight-gain during adulthood was strongly associated with lower ALS; for an additional 1kg gain in weight/year, the RR = 0.43 (95% CI: 0.28–0.65; p  < 0.001). Associations persisted when adjusted for diabetes at enrollment, restricted to never-smokers, and ALS deaths in the 5 years after enrollment were excluded (accounting for recent weight loss). Conclusions : These findings confirm somewhat conflicting, underpowered evidence that adiposity is inversely associated with ALS. We newly demonstrate that weight-gain during adulthood is strongly predictive of lower ALS risk.